General and disease-specific quality of life in patients with chronic suppurative otitis media: a prospective study - Baumann, Ingo; Gerendas, Bianca S.; Plinkert, Peter K.; Praetorius, Mark (Health and quality of life outcomes, 2011)
Chronic suppurative otitis media (CSOM) is frequently associated with symptoms of inflammation like discharge from the ear or pain. In many cases, patients suffer from hearing loss causing communication problems and social withdrawal. The objective of this work was to collect prospective audiological data and data on general and disease-specific quality of life with validated quality of life measurement instruments to assess the impact of the disease on health-related quality of life (HR-QOL).